2017
DOI: 10.1111/and.12891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ivermectin and its combination with alpha lipoic acid on expression of IGFBP-3 and HSPA1 genes and male rat fertility

Abstract: This study was conducted to evaluate the effects of ivermectin (IVM) with therapeutic dose (injected with 0.56 mg/kg b.wt.) either alone or combined with alpha lipoic acid (ALA) (50 mg/kg b.wt daily) on expression of testicular insulin-like growth factor binding protein-3 (IGFBP-3) and heat-shock protein A1 (HSPA1)) genes in the testes, as well as on male rat fertility parameters. Results revealed that expression levels of IGFBP-3 and HSPA1 were significantly increased in testis of the IVM-treated group relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Indeed, previous studies indicated that ivermectin exhibited adverse effects on male reproduction. [33][34][35] Ivermectin treatment caused a reversible reduction of testicular volume and seminiferous tubular diameter, and disturbed the spermatogenesis in rats, all while not affecting the production of testosterone. 34 Ivermectin injection induced a reduction of sperm number, sperm motility as well as serum testosterone level in rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, previous studies indicated that ivermectin exhibited adverse effects on male reproduction. [33][34][35] Ivermectin treatment caused a reversible reduction of testicular volume and seminiferous tubular diameter, and disturbed the spermatogenesis in rats, all while not affecting the production of testosterone. 34 Ivermectin injection induced a reduction of sperm number, sperm motility as well as serum testosterone level in rats.…”
Section: Discussionmentioning
confidence: 98%
“…[33][34][35] Injection of ivermectin in rats significantly decreased the testosterone level, sperm number and motility, and testes weight. 33,35 Ivermectin injection significantly suppressed spermatogenesis of rats. 34 Thus, it is likely that ivermectin would facilitate the anti-fertility effect with EP-1 in sterilizing rodents.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown previously that ALA mediates its beneficial effects by activating the HSR. However, these investigations were focused on a limited set of HSPs; namely HSP25, HSP60, HSP72, HSF1 and GRP75 27,33,34 . Our previous in vivo and in vitro investigations confirmed a novel role of DNAJB3 in reducing metabolic stress, improving insulin signaling and promoting glucose uptake 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the study identified a decrease in sperm parameters including sperm motility and count, it possessed serious limitations, including a lack of control group. Some other studies have shown ivermectin to be gonadotoxic in animal models 61 , but there have been no definitive findings to suggest that ivermectin is associated with male infertility in humans. Attention should be brought to the consequences that future medications used for COVID-19 treatment may have on fertility.…”
Section: Covid-19 Medical Interventionsmentioning
confidence: 96%